(untitled) (Journal of Surgical Sciences, 2020)
The kidney is the most commonly injured genitourinary organ. Most injuries can be managed conservatively but nephrectomy may be needed in case of shuttered or avulsed kidney. Here we present a case of haematuria with blunt trauma to the abdomen. The patient was haemodynamically unstable and his abdomen was distended and rigid. FAST revealed intraabdominal and retroperitoneal haematoma with left renal injury. After rapid primary management emergency nephrectomy had done as there were multiple lecerations and avulsion in the left kidney. Post operative recovery and subsequent follow up was uneventful. Journal of Surgical Sciences (2019) Vol. 23 (1) : 37-39